Dataset- Anisotropic magnetic interactions in a candidate Kitaev spin liquid close to a metal-insulator transition - Ma, Z; Kaib, D A S; Coldea, A I (University of Oxford, 2024)
This data set accompanies the publication entitled "Anisotropic magnetic interactions in a candidate Kitaev spin liquid close to a metal-insulator transition" posted on the archive (https://arxiv.org/abs/2407.15657) and also to appear in Communication Physics. These data were generated by firstly performing X-ray diffraction on single crystals of RuI3. The torque experiments were performed using piezocantilevers and a single axis rotator in a 16T PPMS cryostat at different temperatures. The detailed measurements were performed for three different plans of rotations. The data were analyzed using Fourier decomposition of the contribution to the torque signal as well as direct fitting using an empirical expression described in the text. The experimental data are compared with theoretical simulation using parameters described in the text.